Predictors of difficult airway in the obese are closely related to safe apnea time! - Aparna Sinha; Lakshmi Jayaraman; Dinesh Punhani (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: We aimed to redefine the preoperative factors that may challenge the airway and safe apnea time (SAT) in the obese. Material and Methods: We analyzed 834 patients with body mass index (BMI) >35 kg/m2 for their difficult airway score (DASc). DASc is a consolidation of measures of difficult airway like mask ventilation, difficult intubation, change of device, and number of personnel required. DASc varied from "0" no difficulty to "12" serious difficulty and DASc ≥6 was considered difficult. Preoperative parameters - neck circumference (NC), BMI, STOPBANG score, Mallampati score, obstructive sleep apnea grade, and waist circumference- were assessed. Results: Receiver operating characteristic curve was used to identify risk factors for obese patients at DASc ≥6. The Youden index (for the best threshold, with highest sensitivity and specificity) was BMI 45 kg/m2 and NC 44.5 cm. Their absence had an 81% negative predictive value to include a difficult airway, while their presence had a positive predictive value of 55%. This further has sensitivity of 66% and specificity of 73%. The mean SAT (256 ± 6 s) was inversely related to DASc (P < 0.001). Conclusion: This study demonstrates that BMI and NC have a strong association with difficult airway in obese patients and are inversely related to SAT. Amongst these NC is the single most important predictor of difficult airway in obese and should be used as a screening tool.